Assessment culture in highly effective schools in the Autonomous Community of the Basque Country - Izaskun Lopetegi-Mendizabal; Verónica Azpillaga-Larrea; Luis Lizasoain Hernández (International Journal of Evaluation and Research in Education (IJERE), 2026)
The aim of the present study is to analyze the relationship between assessment culture and school effectiveness in schools identified as being highly effective in the Autonomous Community of the Basque Country (ACBC). In the first (quantitative) phase, 32 highly effective schools were selected using multilevel regression statistical procedures with hierarchical linear models. In the second (qualitative) phase, 90 semi-structured interviews were conducted with members of the management teams, inspectors and key consultants at the selected schools, focusing on a set of previously-established categories. In this paper, we analyze the categories linked to assessment. The results of the analysis suggest that highly effective schools use different formative assessment approaches to improve teaching and learning: data-driven decision making (DDDM), data-based decision making (DBDM), and assessment for learning (AfL). These approaches are developed differently in the two educational stages studied. A proposal is therefore made for helping them to move forward in this sense.